2016
DOI: 10.3201/eid2212.160467
|View full text |Cite
|
Sign up to set email alerts
|

Baylisascaris procyonisRoundworm Seroprevalence among Wildlife Rehabilitators, United States and Canada, 2012–2015

Abstract: Baylisascaris procyonis roundworms can cause potentially fatal neural larva migrans in many species, including humans. However, the clinical spectrum of baylisascariasis is not completely understood. We tested 347 asymptomatic adult wildlife rehabilitators for B. procyonis antibodies; 24 were positive, suggesting that subclinical baylisascariasis is occurring among this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Participants (149/150) filled out a questionnaire on demographic characteristics and potential risk factors, such as pet ownership, pet and wildlife feeding practices, past contact with raccoons or raccoon feces, and frequency of raccoon observations around their neighborhood and residence (Technical Appendix 1). We deidentified samples (Technical Appendix 2) and tested them for B. procyonis IgG by using a recombinant B. procyonis repeat antigen 1 protein Western blot assay, which has 88% sensitivity and 98% specificity ( 3 , 8 ). We generated prevalence estimates by using EpiTools ( 9 ), calculating 95% confidence limits (CLs) for an imperfect diagnostic assay ( 10 ).…”
Section: The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Participants (149/150) filled out a questionnaire on demographic characteristics and potential risk factors, such as pet ownership, pet and wildlife feeding practices, past contact with raccoons or raccoon feces, and frequency of raccoon observations around their neighborhood and residence (Technical Appendix 1). We deidentified samples (Technical Appendix 2) and tested them for B. procyonis IgG by using a recombinant B. procyonis repeat antigen 1 protein Western blot assay, which has 88% sensitivity and 98% specificity ( 3 , 8 ). We generated prevalence estimates by using EpiTools ( 9 ), calculating 95% confidence limits (CLs) for an imperfect diagnostic assay ( 10 ).…”
Section: The Studymentioning
confidence: 99%
“…For example, a recent study showed that 7% of wildlife rehabilitators had Baylisascaris -specific antibodies ( 3 ). Large and heavily infected raccoon populations probably contaminate many regions with B. procyonis eggs ( 1 ).…”
mentioning
confidence: 99%
“…The wildlife rehabilitation community is a diverse group that has different educational and training backgrounds, and as such, their safety practices and awareness of potential occupational hazards may vary. Recently, we demonstrated that 7% (24/347) of healthy, adult wildlife rehabilitators were positive for antibodies to Baylisascaris , indicating prior infection, possibly associated with occupational activities (Sapp et al., ). Positive individuals generally lacked consistent hand‐washing and glove use while handling live raccoons, dead raccoons and after potential faecal contact (Sapp et al., ).…”
Section: Introductionmentioning
confidence: 98%
“…Recently, we demonstrated that 7% (24/347) of healthy, adult wildlife rehabilitators were positive for antibodies to Baylisascaris , indicating prior infection, possibly associated with occupational activities (Sapp et al., ). Positive individuals generally lacked consistent hand‐washing and glove use while handling live raccoons, dead raccoons and after potential faecal contact (Sapp et al., ). Furthermore, a small study of rehabilitated raccoons found that 37% and 56% of raccoons at two centres had patent B. procyonis infections (Kimball, Young, Keith, Kazacos, & Sakanari, ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation